Financial constraints of ASEAN firms: impact alleviation by ESG pillars - Ng, Yee Ling; Lau, Wei Theng; Soh, Wei Ni; Ab Razak, Nazrul Hisyam (Conscientia Beam, 2024)
The purpose of this study is to examine whether ESG plays a positive moderating role in the negative relationship between financial constraint, the Kaplan-Zingales (KZ) and Whited and Wu (WW) indexes, and f irm performance: Return of Asset (ROA) and Return of Equity (ROE). This study uses information from the Thomas Refinitiv database, which covers the Association of Southeast Asian Nations (ASEAN-5): Indonesia, Malaysia, Singapore, Tha iland, and the Philippines non-financial firms from 2011 to 2019. Fixed-effects (FE) are used as the baseline model, and random-effects (RE) act as the robustness of methods. The results show that the main effect of financial constra ints is to a ct as an obstacle to firm performance. However, the marginal effects of financial constra ints can be improved in the presence of ESG. Firms with a high ESG score are better at alleviating the adverse impact of f inancial constraints as compared to those with a low ESG score. When the ESG score is further broken down into three sub-pillar dimensions, the S-score is of the greatest magnitude in its moderating role in the ESG breakdown. The findings have important implications: effective financial support and the source of funding from the government are crucial to supporting firm performance. ESG-compliant strategies should also be formulated to encourage ESG disclosure, which leads to increased capital allocation efficiency. The firms should be stringent on S-score, which helps drive the company a s employees respond by giving their best. Governments and firms need to deploy ESG guidelines in order to succeed in thriving competitive firm performances.